Correlation of Serum Creatinine with TSH in Patients with Primary Hypothyroidism - Anil Chandra; Chethan Subramanya (Journal of Pharmacy and Bioallied Sciences)
Aim: To evaluate the correlation between serum creatinine and thyroid-stimulating hormone (TSH) in patients with primary hypothyroidism. Methods: A cross-sectional study was conducted from October 2022 to April 2024 at Justice K.S. Hegde Charitable Hospital, Nitte. Sixty-two hypothyroid patients were included. Clinical data, including serum TSH, creatinine, and eGFR, were analyzed using SPSS 26.0, employing Spearman correlation and Mann–Whitney tests. Results: The study included 62 patients (82.3% female, 17.7% male; mean age 43.56 years). Primary hypothyroidism was observed in 61.3%, subclinical in 22.6%, and overt in 16.1%. Mean TSH, creatinine, and eGFR were 9.05 μIU/mL, 0.87 mg/dL, and 85.55 mL/min/1.73m2, respectively. While a positive correlation between TSH and creatinine/eGFR was observed, it was not statistically significant. Conclusion: Although TSH showed a positive but nonsignificant correlation with creatinine and eGFR, findings highlight the thyroid–kidney interaction. Further research is needed to assess long-term thyroid effects on renal function.